청폐사간탕(淸肺瀉肝湯)과 단미(單味)들이 Hypoxia-Reoxygenation에 의해 손상받은 Mouse Neuroblastoma 2a Cells에 미치는 영향(影響) - 문하경; Ha Kyoung Moon; 김종우; Jong Woo Kim; 강철훈; Chul Hun Kang; 황의완; Wei Wan Whang (동의신경정신과학회지, 2005)
Object : This study was designed to assess effect of Chungpesagan-Tang and herbs on Mouse neuroblastoma 2a cells damaged by hypoxia-reoxygenation. Method : Mouse neuroblastoma 2a (N2a) cells were measured by MTT assay and LDH assay after 48h hypoxia and 6h reoxygenation. Mouse neuroblastoma 2a (N2a) cells were treated by Chungpesagan-Tang and herbs. Result : In MTT assay of hypoxia all of herbs were almost ineffective and Hubak was a little effective. 2. In MTT assay of reoxygenation most of herbs were not effective. But Hubak was some effective. 3. In LDH assay of hypoxia all of herbs were effective. Especially Chungpesagan-Tang were equally effective on all of concentration. 4. In LDH assay of reoxygenation all of herbs were generally effective. Especially Chungpesagan-Tang and Baekji were highly effective and Kilkyung was also effective on low concentration. 5, The herbs were generally effective on LDH assay of hypoxia and reoxygenation. Conclusion : The results suggest that Chungpesagan-Tang and all of herbs may have protective effect on condition of oxidative stress and can be applied on the development of a new medicine for neurodegenerative disease like dementia.